2012
DOI: 10.1186/1297-9716-43-50
|View full text |Cite
|
Sign up to set email alerts
|

Improved strategy for phylogenetic analysis of classical swine fever virus based on full-length E2 encoding sequences

Abstract: Molecular epidemiology has proven to be an essential tool in the control of classical swine fever (CSF) and its use has significantly increased during the past two decades. Phylogenetic analysis is a prerequisite for virus tracing and thus allows implementing more effective control measures. So far, fragments of the 5´NTR (150 nucleotides, nt) and the E2 gene (190 nt) have frequently been used for phylogenetic analyses. The short sequence lengths represent a limiting factor for differentiation of closely relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 36 publications
3
70
0
1
Order By: Relevance
“…3) whereas in E2 and NS5B tree it has been grouped with 1.2 isolates which shows that grouping of group 1 isolates was not proper. The same observation was also demonstrated by Postel et al [17] for isolates belonging to individual subgenotypes of 1.1, 1.2, 2.1 and 2.3. Due to advantage and disadvantages of each region, Paton et al [16] advised to study different genomic regions whenever new isolates are included in the analyses that fall into new or distinct clusters and also when comparing very similar viruses.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…3) whereas in E2 and NS5B tree it has been grouped with 1.2 isolates which shows that grouping of group 1 isolates was not proper. The same observation was also demonstrated by Postel et al [17] for isolates belonging to individual subgenotypes of 1.1, 1.2, 2.1 and 2.3. Due to advantage and disadvantages of each region, Paton et al [16] advised to study different genomic regions whenever new isolates are included in the analyses that fall into new or distinct clusters and also when comparing very similar viruses.…”
Section: Discussionsupporting
confidence: 84%
“…On the phylogenetic tree, all the Indian isolates were placed in separate cluster from the other members of the 2.2 subgroup from Germany, Austria and Netherlands and had 3.5-10.4 % divergent from them. Interestingly, Indian clade showed a closer phylogenetic relationship to E2-encoding sequences of the Chinese recombinant isolate ''strain 39'' (possessing an E2 gene from an unknown parental 2.2 genotype isolate [17]) at a genetic distances of 3.3-4.6 % than to those of E2-encoding sequences of isolates from Germany(JQ411560), Austria(CSF00740) and Netherlands(AF1829110). Present isolates were 17.1-19.8 % divergent with vaccine strain (HCLV India) and 17.1-24.0, 19.1-24.8 % divergent from the members of the groups 1 and 3 respectively in E2 sequences (Table 1).…”
Section: Phylogenetic Analysis Based On the E2 (190 Nt) Sequencesmentioning
confidence: 99%
“…The figure was taken from Liu, Xia, Wahlberg, Belak, and Baule (2009). review. For more information on genotypes, we refer to corresponding publications ( Jenckel et al, 2014;Luzzago et al, 2014;Pan et al, 2005;Paton et al, 2000;Postel et al, 2012;Rosamilia et al, 2014).…”
Section: Taxonomy Hosts and Diseases 21 Taxonomy: Approved And Tenmentioning
confidence: 99%
“…-6]. It has been reported that subgenotype 2.1 isolates are distributed in many Asian and European countries and play a dominant role in CSF outbreaks occurring in China, Korea and other countries [3,5,7,8]. With more sequences of 2.1 isolates deposited in the GenBank database, CSFV subgenotype 2.1 has been further divided into 10 sub-subgenotypes (2.1a-2.1j) based on a nucleotide sequence of 190-nt and the 1,119-nt E2 gene [8].…”
mentioning
confidence: 99%
“…The ORF encodes a 3898-amino-acid polyprotein that can be further processed to four structural proteins (Core, E rns , E1, and E2) and eight nonstructural proteins (N pro , P7, NS2, NS3, isolate for GD19/2011 is the sub-subgenotype 2.1a strain Paderborn from Germany [5], and the most distant isolate is the sub-subgenotype 2.1d strain IND/AS/GHY/G4 collected from India [7]. Sequence identity values from the comparison of GD19/2011 and other subgenotype 2.1 isolates at the genome and individual gene levels are shown in Table 1.…”
mentioning
confidence: 99%